Persistence of Selected Pyrethroids in the Cocoa Ecosystem and its Toxicity on the Black Cocoa Ant, Dolichoderus Thoraocus Smith (Hymenoptera: Formicidae) - Ginting, Sulaiman (2001)
The persistence of pyrethroids in the cocoa ecosystem and its toxicity on the black cocoa ant Dolichoderus thoracicus Smith (Hymenoptera: Formicidae) were studied in a series of experiments using chemical assay through gas chromatography and biological assay using D. thoracicus workers. Samples of soil were taken from an estate in Sabah from plots that had been subjected to different regimes of pyrethroid application labelled low, moderate and frequent, and compared with soil taken from an area with no history of pyrethroid usage (control). Both the chemical and biological assays showed that the pyrethroids were present in larger amounts and caused higher mortality in the order: frequent >moderate> low >control. The role of light on the degradation of cypermethrin on leaf litter and in soil was examined. Samples of leaf litter treated with 0.011 % cypermethrin solution were exposed to various light intensities and then chemically and biologically assayed at various times after treatment. At the end of the experiment, under light intensities of 200, 2000, 4000, 6000 and 8000 Lx the degradations rates of cypermethrin residue were 16,42,55,67 and 87% respectively; the mortality rates of D. thoracicus were 89, 68, 47, 32 and 12% respectively. A similar experiment was carried out using 500 g soil treated with 125 ml of 0.011% cypermethrin solution. The degradation rates at the end of the experiment at light intensities of 200,2000,4000,6000 and 8000 Lx were 13, 16, 22, 35 and 43% respectively; the mortality rates of D. thoracicus were 99, 96, 85, 69 and 18% respectively. Light therefore plays an important role in the degradation of cypermethrin and the degradation was influenced by intensity and time of exposure.